Obesity and abdominal wound healing in rats - Biondo-Simões,Maria de Lourdes Pessole (2010)
INTRODUCTION: Treatment for obesity essentially has to do with weight loss, which can be achieved through surgical procedures. Despite the considerable rise in the number of such procedures, the relationship between obesity and the healing process has not been totally clarified. PURPOSE: To investigate abdominal wound healing in obese Wistar rats on the seventh and fourteenth days following a laparotomy. METHODS: Thirty-six Wistar rats were randomly distributed into two groups, the control and experiment group. The control group were fed on either a standard diet for the species and the experiment group were put on a high calorie diet. After 116 days, all the animals were submitted to a laparotomy followed by laparorrhaphy. After euthanasia on the seventh or fourteenth day, fragments of the abdominal wound containing the scar were submitted to histopathological and tensiometric analysis. RESULTS: The average weight of the animals from the experiment group was higher than that of the control group (p<0.001). The difference in the resistance of the cutaneous scars was not significant. The aponeurotic scars were more resistant in the control group after seven days (p=0.011) and fourteen days (p=0.040). There was no difference in terms of intensity of the inflammatory reaction and the collagen density was similar in both groups. CONCLUSION: In rats, obesity lowered the resistance of the aponeurotic scars but not the skin scars. It did not interfere with the delayed inflammatory response and the collagen density.